Online political hate speech in Europe: the rise of new extremisms - Ziccardi, Giovanni (Edward Elgar Publishing, 2020)
-- 1. Introduction: The rise of political hate speech online -- Part I. Political hate speech in Europe -- 2. The nature, and a first definition, of political hate speech -- 3. Political hate speech between Europe and usa -- 4. Hate speech: The role and responsibilities of political leaders according to the council of Europe -- Part II. Political hate speech online -- 5. Political hate speech and the new framework of digital networks -- 6. The typical Contents of political hate speech online -- 7. An overview of European online political hate -- 8. Politics online and the use of hate speech -- 9. The instant communication of political hate speech -- 10. Political hate speech and the use of big data -- 11. The distortion of the democratic balance -- 12. Contrasting political hate speech online -- 13. Conclusions: the future of political hate speech online -- Index.